VARIABILIDADE DA PLUMA DO RIO AMAZONAS NA COSTA DO MARANHÃO, MARGEM EQUATORIAL BRASILEIRA - BARROS, Walterly Saraiva (2021)
River plumes are important means of transporting sediments, nutrients and even pollutants from the continent to the ocean, affecting the morphodynamic and biogeochemical characteristics of the region where it disperses, which makes its study of high importance. The plume of the Amazon River presents great variability due to oceanographic strength throughout the year. To detect this variability, modis-aqua adg443 and synthetic salinity products obtained from SeaWiFS adg443 were used, where a specific algorithm was applied where salinity values lower than or equal to 30 g.kg-1 were considered plume. Such data were then useful for time series composition, followed by EOFs and principal component analysis. To apply the EOF, the seasonality of the data was removed and the anomaly was used for the final analysis. Seasonally, from February to May, the plume of the Amazon River changes to the east, reaching the Continental Shelf of Maranhão, and from July to September, the plume strays from the South American coast, after the retroflexion of the Brazilian northern current. following the equatorial north countercurrent. The two calculated EOFs and their Main Components show positive and negative correlations around the mouth of the Amazon River and relationships with extreme weather events from 2014 to 2017, with increased precipitation and consequent increase in feather dispersion by the Brazilian Equatorial Margin.